1986
DOI: 10.1128/iai.53.3.505-510.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a serotype-specific antigen from Pasteurella haemolytica A1

Abstract: Recombinant plasmids coding for a soluble (or surface) antigen ofPasteurella haemolytica Al were identified. Two plasmids, both containing the same 5.4 kilobase pairs of insert DNA, were recovered independently by screening a clone bank of P. haemolytica Al genomic DNA in Escherichia coli for the expression of P. haemolytica Al soluble antigens (R. Y. C. Lo and L. A. Cameron, Can. J. Biochem. Cell Biol. 64: [73][74][75][76] 1986). E. coli cells carrying the plasmids were found to be agglutinated by an antiseru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Al-derived insert in plasmid pPHAl (Table 1). These results support the data obtained in an earlier study using P. haemolytica typing antisera obtained from a different source to detect PHAlSAA expression (22). Additional results showed that the serotype 2-derived D N A insert in pPGA2 similarly expressed the PHAlSAA to a high level on the surface of E. coli.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Al-derived insert in plasmid pPHAl (Table 1). These results support the data obtained in an earlier study using P. haemolytica typing antisera obtained from a different source to detect PHAlSAA expression (22). Additional results showed that the serotype 2-derived D N A insert in pPGA2 similarly expressed the PHAlSAA to a high level on the surface of E. coli.…”
Section: Discussionsupporting
confidence: 90%
“…Isopropylthio-P-D-galactoside (IPTG) and 5-bromo-4-chloro-3-indolyl-!3-D-galactoside (X-gal) were purchased from I'roinega (Madison, WI). Plasmid pPHAl consists of a 3.6 kbp fragment of a PHAlSAA-coding insert subcloned in pBR322 (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA fragments coding for P. haemolytica A1 soluble antigens were isolated using an immunological detection procedure as described [24]. Particular recombinant clones expressing the P. haemolytica A1 leukotoxin [19], a serotype-1 specific antigen [22,25] and the glycoprotease [23] have been identified and reported separately. The nucleotide sequences of the cloned P. haemolytica A1 DNA were analyzed using the Pustell Sequence Analysis Software (International Biotechnology Inc.) and the genes lktC, lktA, lktB, lktD, ssaI and gcp have been identified.…”
Section: Methodsmentioning
confidence: 99%